ISNAD DAN PENGARUHNYA TERHADAP STATUS HADIS - M. Noor Sulaiman PL (Hunafa: Jurnal Studia Islamika, 2005)
This paper deals with the system of isnad (the uninterrupted chain of authorities on which a hadith or tradition is based) and its influence to the status of the hadith. In the science of hadith, this issue is highly necessary since the quality and validity of the hadith can be recognized by the connectedness and continuation of its transmitters (rawi), in addition to the good quality of its transmitter in terms of conduct, honesty, memory, etc. Because of the influence of the system of isnad, various terms of the hadith emerge, such as muttashil, musnad, mursal, munqathi', mu'addhal, mu'allaq, and so on. Moreover, isnad also plays a role in strengthening a hadith, which is weak from other chain, but supported by another hadith, which is strong in terms of its transmitters. In the science of fiqh, the differences in the quality of hadith in turn contribute to the difference of opinions in Islamic law.Kata kunci: Status hadis, sanad, hadis mursal,